a study on acute - and subchronic toxicity of xanthan gum on white swiss mice - Hanh, Vu Van; Nguyet, Nguyen Thi; Huong, Nguyen Minh; Thanh, Hoang Ngoc; Hang, Ngo Thanh; Chi, Ngo Kim; Hoan, Nguyen Van (Academia Journal of Biology, 2015)
Xanthan gum is a polysaccharide that have many important properties in food processing and cosmetic additives. It is a beneficial source of fiber admitted by the FDA for use in human. Xanthan has been successfully produced and purified from liquid fermentation of Xanthomonas campestris Xan0813. In this study, the acute and subchronic toxicity of xanthan gum have been tested and evaluated. The rerults showed that by oral administration of xanthan on Swiss mice at a dose of 1,500 mg/kg, the LD50 value was not determined. At a dose of 250 mg/kg/day for 21 continuous days on Swiss mice  didn’t affect the normal increment of body weight of mice didn’t change hematological indices, red blood cell, white blood cell, platelet and hemoglobin contents, hepatic indices (glutamic oxaloacetic transaminase (GOT), glutamate-pyruvate transaminase (GPT)), renal indices (urea, creatinin levels) were within normal limits.